OPTIMIZACIÓN DEL DETECTOR DE LATIDO FETAL: EMPLEO DEL MICROCONTROLADOR DS87C550. - Cañas, Antonio Jiménez (Revista Cubana de Física, 2005)
Adaptation criteria and processing of Ultrasonic Doppler signal employed in Fetal Heart Detector are presented, starting from the use of D87C51 microcontroller. In the same way, the characteristics of the autocorrelation algorithm optimized as well as the obtained results are shown. Additionally, for the sake of reducing consumption, volume and material resources, the advantages derived of the employment of the new generation DS87C550 microcontroller are considered. It's completely compatible with the previously used and introduces new possibilities in the design.